Incidence of perioperative respiratory complications in patients undergoing elective open upper abdominal surgery under general anaesthesia: Smokers versus non-smokers - An observational study - Sengupta, Sourabh; Mukherjee, Maitreyee; Dasgupta, Prasenjit; Chatterjee, Sajib; Bhattacharya, Dipasri (Asian Journal of Medical Sciences, 2022)
Background: Smoking has various deleterious effects and peri-operative complications. Pulmonary complications following abdominal surgery are frequent and associated with increased morbidity and mortality and length of hospital stay. Aims and Objectives: Hence, this study was done to observe the incidence of various respiratory and cardiovascular complications in the perioperative period in patients undergoing elective open upper abdominal surgery under general anaesthesia among smokers versus non-smokers. The various complications which are studied are as follows - Arterial desaturation, Severe coughing, Laryngospasm, Bronchospasm, Recurrent apnea, Variations in Mean Arterial Blood Pressure and Heart rates. Materials and Methods: Male patients ASA-I, II or III, aged 20–60 years undergoing elective open upper abdominal surgery under general anaesthesia were selected. They were divided into two groups (during pre-anaesthetic checkup) - smokers (>10 cigarette/day for the past 1 year and continued smoking till admission), non-smokers (who never smoked). General anaesthesia was given according to standard protocol. Results: The smokers had higher incidence of laryngospasm as well as bronchospasm but they were not statistically significant. Smokers had low baseline SpO2; greater fall in SpO2 just after extubation, before sending to PACU and on day 1 which were statistically significant. Smokers had raised MAP just after extubation, on day 1 and day 2 which were statistically significant. Conclusion: Smokers had increased incidences of respiratory and hemodynamic complications than non-smokers.